2011
DOI: 10.1007/s00104-011-2170-0
|View full text |Cite
|
Sign up to set email alerts
|

Beeinflusst bariatrische Chirurgie Sucht und Essstörungen?

Abstract: A precise interdisciplinary evaluation is a prerequisite for deciding between gastric banding and the bypass technique as well as to define the need for preoperative and postoperative psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Das von vielen Adipösen geschilderte "Craving nach und Abhängigkeit von übermäßigem Essen" und Publikationen, die Vergleiche mit anderen Abhängig-keiten (Sport, Alkohol, Nikotin, Drogen) nachweisen konnten [17,18], unterstützten den Ansatz "über-mäßiges Essen" als Sucht bedingt zu betrachten. Neuere Literatur [7,19] attestiert übermäßigem Essen, wie es bei Adipösen auftritt, bereits einhellig Suchtcharakter.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Das von vielen Adipösen geschilderte "Craving nach und Abhängigkeit von übermäßigem Essen" und Publikationen, die Vergleiche mit anderen Abhängig-keiten (Sport, Alkohol, Nikotin, Drogen) nachweisen konnten [17,18], unterstützten den Ansatz "über-mäßiges Essen" als Sucht bedingt zu betrachten. Neuere Literatur [7,19] attestiert übermäßigem Essen, wie es bei Adipösen auftritt, bereits einhellig Suchtcharakter.…”
Section: Discussionunclassified
“…Diese "Sucht"-werte unterscheiden weder die Gesamtgruppe der 8-bis 18-Jährigen noch die adipösen Mädchen und Jungen voneinander. Bei ersteren hat diese ‚Sucht' wenig Relevanz, bei den Adipösen erscheint es plausibel, dass dieses primär auch hormonelle Geschehen [17] in bezug auf Geschlecht keine Unterschiede aufweist.…”
Section: Discussionunclassified
“…This should not be understood as the craving for sweet or fat, but simply for excessive eating, which, as far as the intensity of the desire is concerned, does not differ from other addictions such as alcohol or nicotine dependency, compulsive gambling or even addiction to sports (Ardelt-Gattinger et al 2000a, b, 2003Franke 1995). Nine independent studies have shown that the same holds true for children and adolescents of the age group between 8 and 18 (Ardelt-Gattinger and Meindl 2010Meindl , 2011a. According to these, obese people have a deficiency of dopamine receptors similar to that of people addicted to heroin and alcohol (Wang et al 2004;Volkow et al 2002).…”
Section: Obesity: An Addiction We Cannot Completely Abstain Frommentioning
confidence: 93%